Interrupting the symphony: unpacking the importance placed on classical concert experiences. (1st January 2018) - Hess, Juliet
ABSTRACT: The Toronto Symphony Orchestra presents a series of youth concerts each year to introduce and attract younger audiences to the symphony. Music teachers often attend these concerts with students, and the importance of such experiences is frequently emphasised and normalised. This article explores the historical roots of the following relations, attitudes, and practices: (1) the tendency of teachers to privilege Western European music in the curriculum; (2) the attitude that classical music is somehow 'good for' students; (3) the race relations that operate within a youth symphony concert; and (4) the normalisation of Western classical music in music programmes and concert-going choices. Drawing on Asante's [1991. "The Afrocentric Idea in Education." The Journal of Negro Education 60 (2): 170-180] concept of Afrocentric education, I look to pedagogical choices made by participants of a multiple case study in Toronto, Canada to make implications for how music educators might (1) select a wide range of music that include, but are not limited to, classical music; (2) situate such experiences within a broader global, sociopolitical context; (3) consider these Western classical concert experiences as one musical possibility of many; and (4) unsettle the power hierarchies embedded in classroom musical choices.